Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals - Crampton, William G.r.; Albert, James S. (Zootaxa, 2003)
Gymnotus coropinae, a diminutive species of Neotropical electric fish, was originally described by Hoedeman from Surinam. Shortly after its description, G. coropinae was synonymized with a syntopic congener, G. anguillaris. Here we redescribe G. coropinae as a valid species distinguishable from all congeners by a unique color pattern comprised of a dark brown background color marked by 8–18 white or pale yellow bands that in the anterior 1/3 to 2/3 of body are absent or largely restricted to the ventral part of the lateral surface. Gymnotus coropinae is further distinguishable from G. anguillaris and other congeners on the basis of several meristic and morphometric characters. Gymnotus coropinae is widely distributed throughout the Amazon and Orinoco Basins and the Guyana Shield. It inhabits small terra firme forest streams and swamps containing acidic, low-conductivity water.